Fine tuning the composition and nanostructure of Fe-based core-shell nanocatalyst for efficient CO2 hydrogenation - Gupta, Sharad; Jain, Vivek K.; Jagadeesan, Dinesh (Chemnanomat, 2016)
Hydrogenation of CO2 to hydrocarbons is one of the crucial technologies to address the energy deficit and increasing environmental pollution. In this work, we have synthesized and systematically studied the influence of composition and nanostructure of a Fe-based, carbon-coated core shell nanocatalyst. The synthesis method offered good control over the thickness of the carbon coating in the core shell catalyst, which in turn controlled the chemical composition of the core. The results emphasized an optimal amount of Fe3O4, Fe5C2 in the core and partially graphitized carbon in the shell for a high catalytic activity in the conversion of CO2 at atmospheric pressure with higher selectivity to C-2-C-4 olefins.

Facile synthesis of nanostructured Ni/NiO/N-doped graphene electrocatalysts for enhanced oxygen evolution reaction - Madampadi, Roshni; Patel, Avit Bhogilal; Vinod, C. P.; Gupta, Ritu; Jagadeesan, Dinesh (Nanoscale Advances, 2024)
Electrocatalysts containing a Ni/NiO/N-doped graphene interface have been synthesised using the ligand-assisted chemical vapor deposition technique. NiO nanoparticles were used as the substrate to grow N-doped graphene by decomposing vapours of benzene and N-containing ligands. The method was demonstrated with two nitrogen-containing ligands, namely dipyrazino[2,3-f:2 `,3 `-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (L) and melamine (M). The structure and composition of the as-synthesized composites were characterized by XRD, Raman spectroscopy, SEM, TEM and XPS. The composite prepared using the ligand L had NiO sandwiched between Ni and N-doped graphene and showed an overpotential of 292 mV at 10 mA cm-2 and a Tafel slope of 45.41 mV dec-1 for the OER, which is comparable to the existing noble metal catalysts. The composite prepared using the ligand M had Ni encapsulated by N-doped graphene without NiO. It showed an overpotential of 390 mV at 10 mA cm-2 and a Tafel slope of 78.9 mV dec-1. The ligand-assisted CVD route demonstrates a facile route to control the microstructure of the electrocatalysts. Electrocatalysts containing a Ni/NiO/N-doped graphene interface have been synthesised using the ligand-assisted chemical vapor deposition technique.